Vienna blood. [Season 1] [ [videorecording (DVD)] - Beard, Matthew, 1989-; Maurer, Jürgen (Actor); Bullmore, Amelia, 1964-; De Gouw, Jessica, 1988-; Tallis, Frank (PBS, 2020)
1900's Vienna is a hot bed of philosophy, science, and art, where a clash of cultures and ideas collide in the city's grand cafes and opera houses.